Intelligent Plant Cultivation Robot Based on Key Marker Algorithm Using Visual and Laser Sensors - Jiang, Zihan; Shi, Bingyu; Du, Fuyu; Xue, Bowen; Lei, Mingyu; Yang, Ziyi; Sun, Hailong (IEEE sensors journal, 2022)
Intelligent plant cultivation robots play a vital role in plant intelligent cultivation. Aiming at the problem of low accuracy and low efficiency of intelligent plant cultivation robots in searching for target plants in unknown environments, this paper proposes an intelligent plant cultivation robot based on key marker algorithm and improved A * algorithm. In terms of target plant positioning, a key marker algorithm based on YOLOV5 is proposed. Accurately find the target plant in the location environment, mark the key coordinate location of the target plant, and plan the routes. In terms of route planning, the self-node search strategy for the traditional A * algorithm has disadvantages such as many path turning points and large turning angles. By ant colony algorithm and A * algorithm, this paper proposes an improved A * algorithm and combined with DEEPSORT algorithm and YOLOV5 algorithm, the variable path planning is carried out.